Comparative Study for Removal of Zn+2 Ions from Aqueous Solutions by Adsorption and Forward Osmosis - Hussein, Tamara Kawther (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
The aim of this paper was to investigate the removal efficiencies of Zn+2 ions from wastewater by adsorption (using tobacco leaves) and forward osmosis (using cellulose triacetate (CTA) membrane). Various experimental parameters were investigated in adsorption experiment such as: effect of pH (3 - 7), contact time (0 - 220) min, solute concentration (10 - 100) mg/l, and adsorbent dose (0.2 - 5)g. Whereas for forward osmosis the operating parameters studied were: draw solution concentration (10 - 150) g/l, pH of feed solution (4 - 7), feed solution concentration (10 - 100) mg/l. The result showed that the removal efficiency by using adsorption was 70% and the removal efficiency by using forward osmosis was 96.2 %.